2018
DOI: 10.1002/biof.1453
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between platelet count and platelet width distribution and serum uric acid concentrations in patients with untreated essential hypertension

Abstract: These authors contributed equally to this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…There is one piece of previous evidence focusing on the independent association between PDW and UA. Tayefi et al showed a significant positive association between PLT and UA in hypertension patients, and PLT and PDW could be independent determinants of high serum UA in newly diagnosed hypertensive patients. But this study had limitations of restricted case number, not focusing on gender differences, and all cases being hypertensive.…”
Section: Discussionmentioning
confidence: 96%
“…There is one piece of previous evidence focusing on the independent association between PDW and UA. Tayefi et al showed a significant positive association between PLT and UA in hypertension patients, and PLT and PDW could be independent determinants of high serum UA in newly diagnosed hypertensive patients. But this study had limitations of restricted case number, not focusing on gender differences, and all cases being hypertensive.…”
Section: Discussionmentioning
confidence: 96%
“…Accordingly, monitoring some inflammatory and/or oxidative stress markers for cardiovascular diseases (CVDs) including high-sensitivity C-reactive protein (hs-CRP), anti-heat-shock protein 27 (anti-hsp27) antibody titer, prooxidant-antioxidant balance (PAB), uric acid, fasting blood glucose (FBG) appears essential due to their important roles in the incidence and development of CVD. [9][10][11] hs-CRP is an acute phase reactant involved in the atherothrombotic process and is considered the strongest univariate predictor of CVDs. 12,13 Hsp27 is an antiapoptotic agent that interferes with oxidative stress and has a role in activating the immune system, extracellularly.…”
Section: Introductionmentioning
confidence: 99%
“…Another cohort study found that high-sensitivity CRP may serve as a candidate risk predictor for hyperuricemia in middle-aged South Korean men [24], while the association in the older and females has not been reported. However, several studies [22,26] have shown that CRP differ in age and sex. Therefore, the aim of the present cohort study was to explore the longitudinal association between highsensitivity CRP and hyperuricemia in Chinese population.…”
Section: Introductionmentioning
confidence: 99%